A contribution to the Cicadidae fauna of Vietnam (Hemiptera: Auchenorrhyncha), with one new species and twenty new records - Thai, Pham Hong; Yang, Jeng-Tze (Zootaxa, 2009)
According to previous reports, the number of cicada species known from Vietnam is 131; these represent 45 genera. Neotanna yunnanensis Lei et Chou, 1997 and Neotanna sinensis Ouchi, 1938 are transferred to Tanna Distant, 1905 to become Tanna yunnanensis (Lei et Chou, 1997) comb. nov. and Tanna sinensis (Ouchi, 1938) comb. nov., Proretinata vemaculata Chou & Yao, 1986 is transferred to Angamiana Distant, 1890 to become Angamiana vemacula (Chou et Yao, 1986) comb. nov.. Twenty additional species are here recorded for the fauna of Vietnam for the first time: Scolopita lusiplex Chou et Lei, 1997, Hea fasciata Distant, 1906, Hea yunnanensis Chou et Yao, 1995, Katoa chlorotica Chou et Lu, 1997, Mogannia effecta Distant, 1892, Nipponosemia guangxiensis Chou et Wang, 1993, Ambragaeana ambra Chou et Yao, 1985, Balinta tenebricosa (Distant, 1888), Gaeana cheni Chou et Yao, 1985, Gaeana hainanensis Chou et Yao, 1985, Sulphogaeana dolicha Lei, 1997, Paratalainga yunnanensis Chou et Lei, 1992, Formotosena seebohmi (Distant, 1904), Angamiana vemacula (Chou et Yao, 1986), Pomponia backanensis sp. nov., Purana guttularis (Walker, 1858), Tanna yunnanensis (Lei et Chou, 1997), Tanna sinensis (Ouchi, 1938), Euterpnosia ruida Lei et Chou, 1997, Inthaxara flexa Lei et Li, 1996, and Sinosemia shirakii Matsumura, 1927. One of these, Katoa chlorotica, is the first representative of the subfamily Tettigadinae and the tribe Tibicini for Vietnam. One new species, Pomponia backanensis sp. nov., is described and a key to species of Vietnamese Pomponia is provided.